Cooperation Between MYC and β‐Catenin in Liver Tumorigenesis Requires Yap/Taz. Issue 4 (29th July 2020) - Bisso, Andrea; Filipuzzi, Marco; Gamarra Figueroa, Gianni Paolo; Brumana, Giulia; Biagioni, Francesca; Doni, Mirko; Ceccotti, Giorgia; Tanaskovic, Nina; Morelli, Marco Jacopo; Pendino, Vera; Chiacchiera, Fulvio; Pasini, Diego; et al.
Abstract : Background and Aims: Activation of MYC and catenin beta‐1 (CTNNB1, encoding β‐catenin) can co‐occur in liver cancer, but how these oncogenes cooperate in tumorigenesis remains unclear. Approach and Results: We generated a mouse model allowing conditional activation of MYC and WNT/β‐catenin signaling (through either β‐catenin activation or loss of APC ‐ adenomatous polyposis coli) upon expression of CRE recombinase in the liver and monitored their effects on hepatocyte proliferation, apoptosis, gene expression profiles, and tumorigenesis. Activation of WNT/β‐catenin signaling strongly accelerated MYC‐driven carcinogenesis in the liver. Both pathways also cooperated in promoting cellular transformation in vitro, demonstrating their cell‐autonomous action. Short‐term induction of MYC and β‐catenin in hepatocytes, followed by RNA‐sequencing profiling, allowed the identification of a "Myc/β‐catenin signature, " composed of a discrete set of Myc‐activated genes whose expression increased in the presence of active β‐catenin. Notably, this signature enriched for targets of Yes‐associated protein (Yap) and transcriptional coactivator with PDZ‐binding motif (Taz), two transcriptional coactivators known to be activated by WNT/β‐catenin signaling and to cooperate with MYC in mitogenic activation and liver transformation. Consistent with these regulatory connections, Yap/Taz accumulated upon Myc/β‐catenin activation and were required not only for the ensuing proliferative response, but also for tumor cell growth and survival. Finally, the Myc/β‐catenin signature was enriched in a subset of human hepatocellular carcinomas characterized by comparatively poor prognosis. Conclusions: Myc and β‐catenin show a strong cooperative action in liver carcinogenesis, with Yap and Taz serving as mediators of this effect. These findings warrant efforts toward therapeutic targeting of Yap/Taz in aggressive liver tumors marked by elevated Myc/β‐catenin activity.